2017
DOI: 10.3389/fcimb.2017.00397
|View full text |Cite
|
Sign up to set email alerts
|

Legionella Effector AnkX Disrupts Host Cell Endocytic Recycling in a Phosphocholination-Dependent Manner

Abstract: The facultative intracellular bacterium Legionella pneumophila proliferates within amoebae and human alveolar macrophages, and it is the causative agent of Legionnaires' disease, a life-threatening pneumonia. Within host cells, L. pneumophila establishes a replicative haven by delivering numerous effector proteins into the host cytosol, many of which target membrane trafficking by manipulating the function of Rab GTPases. The Legionella effector AnkX is a phosphocholine transferase that covalently modifies hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…Thus, it would be expected that during infection, the Rab35 pool accessed by AnkX remains locked in an inactive GDP-bound conformation, which presumably contributes to inhibition of transferrin recycling. In support of this notion, transferrin recycling was inhibited in macrophages infected with the ΔankX mutant complemented with wild-type AnkX but not when complemented with the catalytically inactive AnkX H229A (Allgood et al, 2017). This directly links post-translational modification of host proteins to an inhibitory effect on recycling endocytosis, but it is unclear if this effect was mediated by targeting other recycling Rabs in addition to Rab35.…”
Section: Legionellamentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, it would be expected that during infection, the Rab35 pool accessed by AnkX remains locked in an inactive GDP-bound conformation, which presumably contributes to inhibition of transferrin recycling. In support of this notion, transferrin recycling was inhibited in macrophages infected with the ΔankX mutant complemented with wild-type AnkX but not when complemented with the catalytically inactive AnkX H229A (Allgood et al, 2017). This directly links post-translational modification of host proteins to an inhibitory effect on recycling endocytosis, but it is unclear if this effect was mediated by targeting other recycling Rabs in addition to Rab35.…”
Section: Legionellamentioning
confidence: 95%
“…Though more is known about how L. pneumophila effectors exploit endoplasmic‐reticulum‐to‐Golgi traffic, how other membrane trafficking pathways might be manipulated is less clear. In a recent study using a pulse‐chase approach, transferrin recycling was found to be drastically diminished in U937 macrophages infected with wild‐type L. pneumophila but not in those infected with a translocation‐deficient mutant (Allgood et al, ). This is consistent with the notion that L. pneumophila disrupts one or more host endocytic recycling pathway because TfR is recycled through both the “fast” and “slow” recycling pathways.…”
Section: Bacterial Pathogens Target Rabs That Regulate Endocytic Recymentioning
confidence: 99%
“…Another L. pneumophila effector protein is AnkX, a phosphocholine transferase that covalently links a phosphocholine moiety to Rab35 [82]. Fluorescent protein-tagged AnkX introduced to mammalian cells was found to localize at the plasma membrane and tubular membrane compartments by transmission electron microscopy [83]. Consistent with its targeting of the endocytic recycling pathway, AnkX co-localized with Rab35 and a Rab35 cargo, the major histocompatibility class I protein (MHCI) [83].…”
Section: Pathogens Use the Rab35 Pathway During Infectionsmentioning
confidence: 99%
“…Zhu et al, 2011). Effectors are responsible for preventing lysosome fusion, recruitment of ER-derived vesicles to the LCV, evasion of the innate immune response, and modulation of a plethora of other host processes to promote intracellular survival and replication of L. pneumophila (Allgood et al, 2017; Bärlocher, Welin, & Hilbi, 2017; Fontana et al, 2011; Horwitz, 1983; Horwitz & Maxfield, 1984; Isberg, O’Connor, & Heidtman, 2009; ubori, Bui, Hubber, & Nagai, 2017; Luo, 2011; C. Price et al, 2017; C. T. Price, Al-Quadan, Santic, Rosenshine, & Abu Kwaik, 2011; Qiu & Luo, 2017; Swanson & Isberg, 1995a, 1995b).…”
mentioning
confidence: 99%